Numerical modeling of concrete beams under serviceability conditions with a discrete crack approach and noniterative solution-finding algorithms - Dias-da-Costa, Daniel (2019)
This paper describes the development and validation of a comprehensive numerical model enabling the simulation of reinforced concrete beams under serviceability conditions using a discrete crack approach. The highly nonlinear behavior introduced by the different material models and the many localized cracks propagating within the member pose a challenge to classic iterative solvers, which often fail to converge. This limitation is solved using a noniterative solution-finding algorithm to overcome critical bifurcation points. The finite element model was validated using experimental data on lightweight aggregate concrete beams under flexural loading. It was shown that the model properly simulates both the overall and localized features of the structural response, including curvature, crack openings, and crack patterns. The model was used to carry out a numerical study of the role of longitudinal reinforcement ratios and crack widths in reinforced concrete beams. It was observed that the total crack openings along a member seem to remain nearly independent of the tensile reinforcement for ratios >2.5% and the same level of strength.